2010
DOI: 10.1182/blood-2009-09-241638
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 and Akt2 promote peripheral B-cell maturation and survival

Abstract: Although the 3 isoforms of Akt regulate cell growth, proliferation, and survival in a wide variety of cell types, their role in B-cell development is unknown. We assessed B-cell maturation in the bone marrow (BM) and periphery in chimeras established with fetal liver progenitors lacking Akt1 and/or Akt2. We found that the gen- IntroductionIn adults, mature B cells derive from a series of precursors in the bone marrow (BM) and periphery. B-lineage committed pro-B cells in the BM undergo V-DJ recombination at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 44 publications
7
73
1
Order By: Relevance
“…Common phenotypic features of p85a-and p110d-deficient mice include an impairment of pro-B cell differentiation, a decrease of splenic B cell populations, and a deficiency of B1 B cells. In comparison, Akt1/2 double deficiency resulted in depletion of marginal zone and B1 B cells, but showed less pronounced effects on transitional and follicular B cells (64). However, Akt3 expression was still intact in these mice.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Common phenotypic features of p85a-and p110d-deficient mice include an impairment of pro-B cell differentiation, a decrease of splenic B cell populations, and a deficiency of B1 B cells. In comparison, Akt1/2 double deficiency resulted in depletion of marginal zone and B1 B cells, but showed less pronounced effects on transitional and follicular B cells (64). However, Akt3 expression was still intact in these mice.…”
Section: Discussionmentioning
confidence: 93%
“…A significant depletion of marginal zone and B1 B cells is also a characteristic feature of SPPL2a 2/2 mice (13). In several of the above-mentioned models, the capability of the antiapoptotic protein Bcl-2 to rescue the respective B cell phenotypes upon transgenic overexpression has been evaluated (57,64,65). Although Bcl-2 expression was able to enhance survival of the knockout B cells, their failure to differentiate and to mature properly was not rescued accordingly, underlining the unique requirement of the individual pathways for B cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, mature B cells were rescued in B-cell antigen receptor (BCR)-negative mice by ectopically expressing a constitutively active PI3K or specifically ablating B-cell PTEN expression (15). Moreover, ectopic Akt1 expression in mouse lymphocytes results in peripheral B and T cells (16), whereas bone marrow chimera mice lacking Akt1 and Akt2 in hematopoietic cells have substantially reduced marginal zone B and B1 cells, similar to PI3K-deficient mice (17). A human lacking the PI3K p85α subunit had a much earlier block in B-cell development than was evident in p85α-deficient mice (18).…”
mentioning
confidence: 99%
“…Genetic studies have shown that Akt1 and Akt2 are needed for the generation of MZ B cells and B1 B cells, but not of follicular B2 cells [12,13]. In addition, Akt2 suppresses the transcriptional activity of FoxO1, which inhibits Rag expression and V(D)J rearrangement in B-cell progenitors and, thereby, affects early B-cell maturation [14].…”
Section: Introductionmentioning
confidence: 99%